The Role of Extracting Solvents in the Recovery of Polyphenols from Green Tea and Its Antiradical Activity Supported by Principal Component Analysis - Koch, Wojciech (Molecules, 2020)
Green tea contains a variety of biologically active constituents that are widely used in the pharmaceutical and food industries. Among them, simple catechins constitute a major group of compounds that is primarily responsible for the high biologic activity of green tea extracts. Therefore, the application of optimized extraction conditions may result in obtaining high value extracts. The main purpose of the study was to compare the content of polyphenols, mainly catechins, and the antioxidant activity of green tea extracts obtained by three different extraction methods: simple maceration, ultrasound extraction and accelerated solvent extraction using six various solvent systems. The quality of the extracts was evaluated by LC-ESI-Q-TOF-MS methodologies and spectrophotometric determinations. The obtained results revealed that catechins’ extraction efficiency was identical for the three techniques studied. However, larger quantitative differences among the samples were observed when using different solvents. The total content of major catechins and gallic acid was within a very wide range of 10.2–842 mg/L. Ethyl acetate was by far the least effective extractant, regardless of the extraction technique used. After all, the solvent system composed of ethanol:water (1:1 v/v) was proven to be the best to recover catechins and to deliver extracts with the highest antiradical activity.